Conduits for esophageal replacement: alternatives - Nichkaode, Prabhat B.; Naik, Tarun; Sharma, Anurag (International Surgery Journal, 2017)
Background: Native esophageal replacement after esophageal resection is a problem that has challenged the surgeons over a century. Conduit must be long enough to bridge between cervical esophagus and abdomen. It must have reliable vascular supply, so that it can perform its function of deglutition. Stomach, colon and jejunum all these are used since long. However, there are times when the stomach is unavailable for use as a conduit. It is in these instances that an esophageal surgeon must have an alternative conduit in their armamentarium. Present study is aimed to discuss technical aspects of stomach, colonic, interposition in 32 cases of benign and malignant pathology, we review recent literature with a focus on outcomes, advantages and disadvantages of all options. Methods: A retrospective study of 32 cases between 2009 to 2016 at teaching institute in central India. 32 cases of benign and malignant esophageal disease needing esophageal resection and replacement. The record of each patient was reviewed for age, gender, indication for esophageal resection, type of operation, indication for selection of conduit, morbidity and mortality. The patient’s gastrointestinal symptoms were graded as excellent, good, fair or poor. Survival was estimated by the Kaplan-Meier method using the date of operation as the starting point. Results: Study includes 24 males and 8 females, 25 cases cancer esophagus with 6 patients caustic stricture, 1 patient had radiation stricture. Gastric conduit was used in 29 patients while 3 patients had colonic interposition. No complications noted in colonic group, while cervical anastomotic leak along with cardiovascular and respiratory complications noted in 6 patients. Gastric replacement was less time consuming than colonic interposition. There was hospital mortality of 4 patients. There is no difference in survival of these patients whether you use gastric or colonic conduit. Conclusions: Clinical decision making in the treatment of esophageal cancer consists of balancing the risks of a particular treatment against potential benefits gained in survival and quality of life. The choice of conduit for reconstruction may have significant impact on the quality of life. Stomach is the most commonly used organ for replacement but when it is not available then colon can safely be used as an esophageal replacement.